What moves you? shaping your dissertation in dance - Nichol, Charlotte; Uytterhoeven, Lise (Routledge, 2017)
Every dissertation is individual and unique - particularly for dance students, who must combine a wide range of approaches into tailor-made research methodology. What Moves You? fosters a creative approach to dissertations and final projects. By guiding the development of a personal study program, this volume encourages dance students to take ownership of their artistic and academic work, a skill essential both to successful undergraduate study, and to making the first steps towards a career in dance. Rather than propose a prescriptive, step-by-step mantra, Charlotte Nichol and Lise Uytterhoeven draw upon contributions from students, teachers, examiners and practitioners to broaden the notion of 'research' and demystify the purpose of the dissertation